(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
The article presents information related to the pressing problem of our time - the epidemic of osteoporosis of the 21st century, developing in people over 50 years of age, especially women, and its main etiological factors. The table also highlights risk factors and predictors of tubular fractures and osteoporosis in perimenopausal women